ANALISIS PERBANDINGAN KINERJA KEUANGAN PADA KOPERASI KONVENSIONAL DAN KOPERASI SYARIAH - Gusniati Puteri; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study aims to determine and analyze the soundness of the liquidity ratios, solvency, and profitability of the Umega Prima Trade and Services Cooperative and the Al-Ittihad BMT Cooperative in Pekanbaru City during the 2014-2018 period. And to find out the fulfillment of the financial performance standards of the Umega Prima Trade and Services Cooperative and the Al-Ittihad BMT Cooperative in Pekanbaru City, based on liquidity ratios, solvency ratios and profitability ratios during the period 2014-2018.This study uses secondary data in the form of data obtained by the author through, manual reports and financial reports of the Umega Prima Trade and Services Cooperative and the Al-Ittihad BMT Cooperative in Pekanbaru City that are needed by researchers for the analysis of liquidity, solvency, and profitability.The results of the analysis show that the analysis of the financial statements of the Trade Cooperative and Prima Umega Services for the period 2014 - 2018 based on Liquidity, Solvency and Profitability Ratios are: 1) Analysis of liquidity ratios, qurrent ratios get the predicate